The relationship between openness to change and job satisfaction in mergers & acquisitions - Bahar, Ventura (My University, 2005)
Globalleşmenin bir sonucu olarak iş dünyası varlığını değişim yaklaşımları ile sürdürmek durumundadır. Günümüzde şirketler sinerji yaratabilmek, rekabete girebilmek, müşterilerine daha iyi hizmet verebilmek ve varlıklarını sürdürebilmek için şirketlerini evlendirmek veya birleştirmek yoluna gitmişlerdir. Son yıllarda şirket evlilikleri Türkiye’de de çok popüler olmuş hızla yaygınlaşmıştır. Bu şirket evlilik ve birleşmeleri bir yandan pazarda rekabeti arttırırken diğer yandan da çalışanlara birçok değişimi ve yenilikleri de beraberinde getirmektedir. Yeni organizasyon şemasının açıklanması ile birlikte yeni pozisyonların oluşması, kişinin kendine daha uygun bir pozisyona transferi veya terfisi olabileceği gibi işten atılması da olasıdır. Bu durumda değişime direnci olan kişi, bu sürecin devam etmesini istemez. Bu nedenledir ki iş tatmini bu süreçle çok önemlidir. İş tatmini az olan personel şirket evlilik - birleşme sürecinde şirket için çok az verimlidir. Çünkü kişinin doğasında olan değişime direnç, belirsizlik nedenleri kişinin verimliliğini düşürür. Bütün bu sebeplerle şirket evlilik ve birleşmelerini bir değişim olayı olarak görüp değişime açıklık ile iş tatmini arasında özellikle de şirket evlilik, birleşme sürecinde bir ilişki olup olmadığını incelemeye karar verdim.Kişilerin değişime açıklık algıları iş tatminini etkiler ve demografiklerin de bu ilişki üzerinde etkileri bulunur.Bu çalışma ile bu ilişki açıklanmaya çalışılmış ve bu ilişkinin varolduğu görülmüştür.

THE RELATIONSHIP BETWEEN OPENNESS TO CHANGE AND JOB SATISFACTION IN MERGERS & ACQUISITIONS As a result of globalization, business world’s existence is dependent on their approach to change.Today companies get in the way of Mergers & Acquisitions in order to continue its existence ,to edge into the market,to serve its customers better and to join into the competition or for developing synergy . In recent years M&As become the latest trend and is deploying rapidly in Turkey.These M&As meanwhile speed up the competition in the market ,it brings lots of innovations and change for the employee.This change process passes with pangs but sometimes it brings lots of innovations for the people who are open to change. There can be positive changes such as new openning positions or to promote or to transfer to a new position which is more vacant for the employee.But there is a possibility to get laid off too.In this situation people who got resistance to change don’t want the process to go on.That’s why job satisfaction is very important issue. An employee who has less job satisfaction is less productive for the company specially in M&A process. Because of these reasons I perceive M&A as an event of change and start to research if there is a relationship between openness to change and job satisfaction in M&As.Person’s perceptions of openness to change effects job satisfaction and demographics have affect on this relation.With the help of this study it has been tried to tell this relation and it is seen a relation between openness to change and job satisfaction.
Keywords: İş Tatmini